Penghindaran pajak perusahaan: Tinjauan literatur - Resca, Yuliana; Munandar, Agus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Tax avoidance is an attempt to legally evade taxes without violating tax laws, with the aim of taking advantage of weaknesses in tax laws to reduce the tax burden. This study seeks to summarize the key findings of tax avoidance studies in the financial accounting literature over the past decade. In determining the existence of tax evasion and the causes and consequences of corporate tax avoidance, we consider theoretical developments and relevant empirical findings on relevant topics. We propose various ideas for further research to explore the under-researched topic of tax avoidance.